(3ThGgO CHjGJ Ydi MQha GdgLGAs - (3TgGH GdOjf eMeO Hf ehLhO SYO LOgs ((3YHO Gddg Hf YHO GdhGMO Hf YHO GddWja Hf YHO GdSdGe GdYHGSi s)
(3ChdgG (B:s
(3hHYO ajbhd TgGH GdOjf eMeO Hf ehLhO gPg fHPg dWjag LYdJgG ai ZQQ GdCeKGd hGdCTYGQ GdJi JOQL ai GdeMGVQGJ s
(3BNQgG (B:s
(3HjJ jHbi JeJ GdThGgO s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B18s
(3GdfSNI HgG MhGTs
(3HgG Jedc HGSe YHO Gddg Hf YHO GdhGMO Hf YHO GddWja Hf TYjH Hf YHO GdSdGe hjQLY JGQjNgG Edi SfI (B1294 (3g`s
(3HgG fXGe GdJYbjHIs
(3eUOQ GbJfGA GdCUd (B:s
(3GdecJHI GdYHGSjI (B_ (3GdHUQI (B(7 (3O(B) s
Keywords: (3GdeLGejYs